Forward-projected Model-based Iterative Reconstruction SoluTion in Temporal Bone Computed Tomography: A Comparison Study of All Reconstruction Modes. Issue 2 (13th March 2021) - Kurokawa, Ryo; Hagiwara, Akifumi; Nakaya, Moto; Maeda, Eriko; Yamaguchi, Haruomi; Gonoi, Wataru; Sato, Jiro; Nakata, Kenta; Ino, Kenji; Ota, Yoshiaki; Kurokawa, Mariko; Baba, Akira; et al.
Abstract : Objective: Identify appropriate reconstruction modes of Forward-projected model-based Iterative Reconstruction SoluTion (FIRST) in temporal bone computed tomography (CT) and investigate the contribution of spatial resolution and noise to the visual assessment. Methods: Sixteen temporal bone CT images were reconstructed. Two blinded radiologists assessed 8 anatomical structures and classified the visual assessment. These visual scores were compared across reconstruction modes among each anatomical structure. Visual scores and contrast-to-noise ratio, noise power spectrum (NPS) at low (NPSLow ) and high (NPSHigh ) spatial frequencies, and 50% modulation transfer function relationships were evaluated. Results: Visual scores differed significantly for the stapedius muscle and osseous spiral lamina, with CARDIAC SHARP, BONE, and LUNG modes for the osseous spiral lamina scoring highest. Visual scores significantly positively correlated with NPSLow, NPSHigh, and 50% modulation transfer function but negatively with contrast-to-noise ratio. Conclusions: Modes providing higher spatial resolution and lower noise reduction showed an improved visual assessment of CT images reconstructed with FIRST.